Motivational changes of cannabis use prior to and during the course of schizophrenia. (22nd December 2016) - Schnell, Thomas; Gliese, Rajac; Schröter, Romy; Kasten, Erich; Gouzoulis‐Mayfrank, Euphrosyne
Abstract : Background and Objectives: We investigated subjective reasons/motivation for cannabis use in patients with schizophrenia ( n  = 51) compared to otherwise healthy cannabis users ( n  = 109). Moreover, we explored possible changes in the motivational patterns of both groups over time. Methods: A questionnaire was developed with six dimensions of motivations to use cannabis: affect regulation, relaxation, habit, structuring everyday life, creativity, and sociability . Participants filled out the instrument regarding their present and initial use of cannabis. Results: At the time of onset of consumption, groups only differed significantly in habit with higher ratings for patients with schizophrenia and cannabis use (SCH+CAN group) and in sociability with higher ratings for otherwise healthy users (CAN group). In respect of present use, the motivation to consume cannabis was significantly higher for affect regulation and structuring everyday life in the SCH+CAN group and for relaxation and sociability in the CAN group. With reference to time‐based variations, the SCH+CAN group reported increased relevance of structuring everyday life over time. Furthermore, the CAN group reported increased importance of habit over time, whereas the SCH+CAN patients showed decreased ratings of habit over time. Conclusions and Scientific Significance: Our findings must be considered preliminary because of the retrospective nature of the assessment. Nevertheless, the present study provides an indication of the time‐dependent variation of cannabis‐use motivation in schizophrenia, which may provide a better understanding of the functions of cannabis use within the population. Results argue for specific motivational based interventions for the group of schizophrenia patients with regular cannabis use. (Am J Addict 2017;26:122–128)